Antimicrobial activity and microbial transformation of ethyl p-methoxycinnamate extracted from Kaempferia Galanga - Omar, Muhammad Nor; Mohd Hasali, Nor Hazwani; Alfarra, Helmi Yousif; Yarmo, Mohd Ambar; Zuberdi, Ahmad Muzammil (Oriental Scientific Publishing Co., 2014)
Ethyl p-methoxycinnamate (EPMC), a major constituent of the Kaempferia galanga rhizome, was transformed to ethyl p-hydroxycinnamate (EPHC) using Aspergillus niger. The EPHC metabolite was elucidated by NMR spectroscopic technique. Antimicrobial microbial study found that EPHC was active against all strains tested with a good minimum inhibitory concentration (MIC). It was active against both Staphylococcus aureus and Bacillus cereus at MIC 333 μg/ml while against Pseudomonas aeruginosa, Escherichia coli and Candida albicans at MIC 111 μg/ml. It was also shown that EPHC exhibited more growth inhibition potential than EPMC. Besides that, EPHC has shown the minimum bactericidal concentration (MBC) toward B. cereus, P. aeruginosa and E. coli at the concentration of 1000 μg/mL while EPMC did not show killing potential toward the tested microorganisms.